Achievement of goal anti‐Xa activity with weight‐based enoxaparin dosing for venous thromboembolism prophylaxis in trauma patients. Issue 6 (7th May 2021) - Taylor, Ashley; Huang, Ellen; Waller, Jennifer; White, Cassandra; Martinez‐Quinones, Patricia; Robinson, Tim
Abstract: Study Objective: The purpose of this study was to evaluate the utility of routine anti‐Xa peak monitoring for trauma patients initiated on weight‐based enoxaparin for venous thromboembolism (VTE) prophylaxis and identify patient populations where monitoring is necessary. Design: Retrospective study. Setting: Augusta University (AU) Medical Center in Augusta, Georgia, a level 1 trauma center. Patients: Adult patients admitted to the trauma surgery service requiring chemical VTE prophylaxis. Intervention: At least three consecutive doses of enoxaparin 0.5 mg/kg subcutaneously every 12 hour for VTE prophylaxis prior to an anti‐Xa peak as the initial chemical VTE prophylaxis strategy. Measurements: The primary end point was the percentage of patients who achieved goal anti‐Xa peak of 0.2–0.6 unit/ml. The incidence of newly diagnosed VTE and clinically significant bleeding were assessed as secondary end points. Main Results: From January 1, 2018, through February 28, 2019, 300 patients met inclusion criteria. Anti‐Xa peaks were within goal in 91% of all patients, 7.7% were below goal, and 1.3% were above goal. For patients who did not meet the goal, dose adjustments were made in 70.4% of patients. New levels were obtained in 73.7% of those patients, and all repeat levels was within goal. Clinically significant bleeding occurred in 5.3% of patients. Newly diagnosed VTE occurred in 1.7% of patients. Conclusions: The use of initial weight‐based enoxaparin dosing in trauma patients routinely achieved the prespecified target anti‐Xa goal. In conclusion, anti‐Xa levels are not necessary for routine monitoring of weight‐based enoxaparin for VTE prophylaxis in trauma patients. Incidence of clinically significant bleeding and newly diagnosed VTE were similar to previous studies.